Integrated Transcriptome and Multiple Activated Pathways in Endometrial Cancer - Jin, Qi; Jiang, Xiaohua; Du, Xin; Hu, Weiping; Bai, Shun; Wang, Xian; Xu, Bo; Zhao, Weidong (Frontiers in Genetics, 2021)
By the incidence of endometrial cancer is up soaring worldwide, it became the leading gynecologic cancer in the United States. Standard treatment made the loss of reproductive function in women of childbearing age. Furthermore, advanced cancer stage was associated with poor overall survival. The aim of this study was to explore the abnormal expression profile of genes during the development of endometrial cancer which is essential to provide a better understanding of the mechanisms involved. Five pairs of endometrial cancer tissues and normal endometrial tissues were involved in this study for next-generation transcriptome sequencing technology. Quantitative real time PCR (RT-qPCR) was performed to validate the expression profile of key differentially expressed (2.0-fold change, adj. p < 0.05) genes (DEGs) from the RNA-seq result. GO and KEGG pathways were analysed by bioinformatics analysis. The transcriptomic sequencing results showed 1153 DEGs, including 673 upregulated and 480 downregulated genes in the EC specimens. Decreased expression of ID1, IGF1, GDF7, SMAD9, TGF-beta and WNT4, as well as GDF5, INHBA and ERBB4 overexpression, were observed in EC using RT-qPCR. Additionally, EC tissue exhibited marked enrichment in genes promoting cellular adhesion, proliferation, migration and plasma membrane. KEGG analysis revealed various pathway changes, such as TGF-beta, PI3K-Akt, Wnt, Estrogen pathways. Our data presented the molecular event involved in the pathogenesis of EC which may as possibly for potential diagnostic marker and therapeutic interventions.